A critical discussion of research on the social acceptance of renewable energy generation and associated infrastructures and an agenda for the future - Batel, S. (Journal of Environmental Policy and Planning, 2018)
Social sciences’ research on the social acceptance of renewable energy generation and associated technologies (RET), such as high voltage power lines, has been growing in the last decades. In fact, while RET are considered one of the main mitigation measures of climate change, opposition to their construction, and namely from the local communities living nearby, is often found. Important conceptual proposals have been made for a better understanding of opposition, however, this literature still presents some limitations. Here, I will discuss two of them: first, the main focus on the local and, with it, the lack of a relational and critical approach, which recognizes opposition and other types of responses to RET as public participation in RET-related issues; second, the focus on the individual and the consequent lack of examining people’s material practices and engagements.